Mirror, Mirror, on the wall, will the market rise or will it fall? A study into the effectiveness of Japanese Candlestick Charting on the Johannesburg Stock Exchange from 2010 to 2019 - Mukansi, Tintswalo (Department of Finance and Tax, 2022)
Using the methodology developed by Caginalp and Laurent (1998), this study tests the predictive ability of eight three-day reversal candlestick patterns on a sample of sixty listed shares on the Johannesburg Stock Exchange (JSE) from 1 January 2010 to 31 December 2019. The study further investigates the predictability of the patterns on three sub-sectors of the JSE; this included the resource, financial and industrial sectors. As the final step, the study tests the use of the candlestick pattern as a trading strategy before and after costs. To the authors knowledge, it is the first study of candlestick patterns on South Africa's JSE. However, similar studies have been conducted in other emerging markets such as Thailand, Taiwan and Brazil. The study finds that only one of the candlestick patterns, the Three Outside Down pattern, has predictive ability on the JSE. However, when looking at the JSE sub-sectors, the results are more divergent. Candlestick patterns have no predictive ability on the resources and financial sector but on the industrial sector three patterns (Three Inside Up, Three Black Crows and Morning Star) were significant at the ten percent level of significance; and the Three Outside Up and Three Outside Down were at the five percent level of significance. The study finds that after fees the use of candlestick patterns is unable to outperform passive benchmarks. The evidence suggests some violations of the Random Walk Theory, but the study finds that the JSE and its sub-indices are weak-form efficient in terms of the Efficient Market Hypothesis. The Thai and Brazilian markets were also found to be weak-form efficient.